Reducing 30-day post gastrostomy insertion mortality with a feeding issues multidisciplinary team meeting. (December 2020) - Bond, A.; Conley, T.; Fiske, J.; Raymond, V.; Young, A.; Collins, P.; Dibb, M.; Smith, P.J.
Summary: Introduction: Decision-making regarding percutaneous endoscopic gastrostomy (PEG) insertion can be complex both medically and ethically. Thirty-day mortality following (PEG) insertion is an important quality indicator for endoscopy accreditation and for service evaluation. It also forms part of the measures assessed within the 'Getting It Right First Time' programme (GIRFT). We aimed to assess the impact of a newly adopted Feeding Issues MDT (FIMDT) and the clinical application of the Royal Free Gastrostomy Score (RFGS). Method: We adopted a retrospective observational methodology to assess the impact of a feeding issues MDT within our trust. The included study period ran from January 2016 to December 2019 (4 years). This formed part of a quality improvement (QI) project initiated upon receipt of the GIRFT report for our NHS trust. Statistical analysis and QI methodology was used to interpret and present the data. Results: Two hundred and sixty eight PEG insertions occurred during the study period. 188 PEGs were inserted prior to the start of FIMDT and 45 following its inception. On average there were 66 PEGs performed per year. There was no significant difference in age for those undergoing PEG insertion pre (68 years) and post (69 years) FIMDT adoption. Prior to FIMDT those that died within 30 days post PEG were significantly older than those who did not (p < 0.001), whilst following FIMDT adoption there was no such difference. Prior to FIMDT the 30-day post PEG mortality was 10.64%, whilst following adoption of the FIMDT the mortality rate fell to 6.6% (p = 0.04). The mean number of procedures performed between a 30-day mortality occurring rose from 7.5 to 13.6. Furthermore, the mean number of days between a 30-day post insertion mortality occurring also rose from a mean of 53.0–111.8, pre and post FIMDT adoption. The Royal Free Gastrostomy Score (RFGS) for those discussed at FIMDT and declined for PEG insertion was significantly higher than those accepted for PEG insertion (p = 0.01). Over the entire study period those who died within 30 days following PEG insertion had a significantly greater RFGS (p < 0.0001). Conclusion: In our trust the adoption of a FIMDT has significantly reduced the 30-day mortality for PEG insertion. We have also demonstrated the clinical utility to assess mortality risk of the RFGS when making decisions around patient suitability for PEG insertion.